Case Report: Central Nervous System Immune Reconstitution Inflammatory Syndrome Related to Bacterial Meningitis - Hu, Mengyan; Liu, Sanxin; Lu, Danli; Zhong, Yi; Yu, Dafan; Qiu, Wei; Lu, Zhengqi; Zhang, Bingjun (Frontiers in Immunology, 2021)
Central nervous system immune reconstitution inflammatory syndrome (CNS-IRIS) describes clinical characteristics that may be observed in previously immunocompromised patients during rapid restoration of immunity function in the presence of a pathogen. There was no reported about CNS-IRIS related to bacterial meningitis. Here, we reported a 24-year-old pregnant female patient with bacterial meningitis. Her clinical condition and neuroradiological worsening after induced labor despite great effective anti-infective therapy. CNS-IRIS was considered. Corticosteroids was administered, and the patient gradually recovered. We present the first case of CNS-IRIS associated with bacterial meningitis.